INDEX VOL 3 N 3 - Navarro Cáceres, María (ADCAIJ: Advances in Distributed Computing and Artificial Intelligence Journal, 2015)
The Advances in Distributed Computing and Artificial Intelligence Journal (ADCAIJ) is an open access journal that publishes articles which contribute new results associated with distributed computing and artificial intelligence, and their application in different areas. The artificial intelligence is changing our society. Its application in distributed environments, such as the Internet, electronic commerce, mobile communications, wireless devices, distributed computing and so on, is increasing and becoming and element of high added value and economic potential in industry and research. These technologies are changing constantly as a result of the large research and technical effort being undertaken in both universities and businesses. The exchange of ideas between scientists and technicians from both academic and business areas is es-sential to facilitate the development of systems that meet the demands of today's society. We would like to thank all the contributing authors for their hard and highly valuable work. Their work has helped to contribute to the success of this special issue. Finally, the Editors wish to thank Scientific Committee of Ad-vances in Distributed Computing and Artificial Intelligence Journal for the collaboration of this special issue, that notably contributes to improve the quality of the journal. We hope the reader will share our joy and find this special issue very useful.